Cerium oxide-copper-cobalt sulfide catalyst as well as preparation method and application thereof

By developing cerium oxide copper-cobalt sulfide catalysts and using rare earth elements to regulate the energy band of copper-cobalt spinel sulfides, the problems of environmental pollution and high cost of precious metal catalysts during the oxidation of traditional aromatic alcohols are solved, and efficient and stable aroma is achieved The alcohol conversion reaction reduces the amount of oxidant used.

CN119243236APending Publication Date: 2025-01-03LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362252.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the oxidation process of traditional aromatic alcohols, a large number of stoichiometric oxidants are required, which leads to environmental pollution. The precious metal catalysts are costly and have limited reserves, making them difficult to widely use in industrial production.

Method used

Develop a cerium oxide copper-cobalt sulfide catalyst to regulate the energy band of copper-cobalt spinel sulfide through the introduction of the rare earth element cerium, improve its stability and selectivity under alkaline conditions, and through electrochemical deposition and oxidation The catalyst is prepared by hydrothermal method to form a nanosheet-like structure to enhance catalytic activity.

Benefits of technology

The performance of efficient catalyzing the conversion of benzyl alcohol to benzaldehyde or benzoic acid under alkaline conditions is achieved, which reduces the amount of oxidant used, improves the stability and selectivity of the catalyst, and reduces the impact on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243236A_ABST
    Figure CN119243236A_ABST
Patent Text Reader

Abstract

The invention provides a cerium oxide-copper-cobalt sulfide catalyst as well as a preparation method and application thereof. The cerium oxide-copper-cobalt sulfide catalyst provided by the invention comprises a conductive substrate and a composite material loaded on the conductive substrate, wherein the composite material comprises cerium oxide and copper-cobalt sulfide. The cerium oxide-copper-cobalt sulfide catalyst provided by the invention is a rare earth metal anode catalyst with high activity, has efficient selectivity and large surface area, and simultaneously has a large number of active sites, so that the cerium oxide-copper-cobalt sulfide catalyst has good catalytic performance of directional conversion from benzyl alcohol to benzaldehyde or benzoic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the intersecting field of electrochemical catalysis and organic synthesis, and specifically relates to a cerium copper cobalt oxide sulfide catalyst and a preparation method and application thereof. Background Art

[0002] Aromatic compounds play an indispensable role in organic synthesis. However, the traditional oxidation of aromatic alcohols to aldehydes or acids requires stoichiometric oxidants, such as chromium, manganese, or ruthenium salts, which can cause great pollution to the environment or oxidize other functional groups, thereby affecting the properties of the compound itself and making it difficult to obtain the desired product. The preparation of aromatic aldehydes or acids by electrooxidation will reduce the use of oxidants, thereby greatly reducing the impact on the environment. Although noble metal catalysts have high catalytic efficiency and strong stability, they are difficult to be widely used in industrial production due to their high cost and limited reserves. Summary of the invention

[0003] One of the purposes of the present invention is to provide a cerium copper cobalt oxide sulfide catalyst, the second purpose is to provide a method for preparing the cerium copper cobalt oxide sulfide catalyst, and the third purpose is to provide the use of the above catalyst in the electrocatalytic oxidation of aromatic alcohols such as benzyl alcohol.

[0004] In a first aspect, the present invention provides a cerium oxide copper cobalt sulfide catalyst, the catalyst comprising a conductive substrate and a composite material supported on the conductive substrate, the composite material comprising cerium oxide and copper cobalt sulfide. In the present invention, by introducing the rare earth element cerium and utilizing the special 4f-5d structure of rare earth metals to regulate the energy band of copper cobalt spinel sulfide, the electro-oxidation reaction of benzyl alcohol of copper cobalt spinel sulfide can be significantly improved, and it helps to improve its stability and high selectivity under alkaline conditions, so that the catalyst of the present invention has excellent electro-oxidation performance of benzyl alcohol to benzaldehyde or benzoic acid.

[0005] According to some embodiments of the present invention, the molar content of cerium element is 1%-45%, for example, 2%, 3%, 4%, 6%, 8%, 10%, 12%, 13%, 15%, 16%, 18%, 20%, 23%, 25%, 27%, 29%, 30%, 33%, 35%, 37%, 39%, 40%, 41%, 43% or any value therebetween, based on the total molar amount of cerium oxide and copper cobalt sulfide. According to some embodiments of the present invention, the molar content of cerium element is 1%-20%, for example, 2%, 3%, 4%, 5%, 6.0%, 6.5%, 6.7%, 7%, 7.5%, 8%, 8.8%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 14%, 17%, 19% or any value therebetween, based on the total molar amount of cerium oxide and copper cobalt sulfide.

[0006] In some embodiments, the molar content of cerium is 5%-15%. In some embodiments, the molar content of cerium is 5%. In some embodiments, the molar content of cerium is 10%. In some embodiments, the molar content of cerium is 15%. In some embodiments, the molar content of cerium is 6.8%-12.1%.

[0007] In some embodiments, the composite material has a heterostructure of cerium oxide and copper cobalt spinel sulfide (copper cobalt sulfide).

[0008] According to some embodiments of the present invention, the composite material has a nanosheet morphology. According to some embodiments of the present invention, the composite material is a hexagonal nanosheet. The nanosheet structure can effectively increase the specific surface area of ​​the catalyst, thereby increasing the electro-oxidation activity of benzyl alcohol.

[0009] According to some embodiments of the present invention, the loading amount of the composite material on the conductive substrate is 1 mg / cm 2 -10mg / cm 2 , for example 1.5 mg / cm 2 , 2.0mg / cm 2 , 2.5mg / cm 2 、3.0mg / cm 2 、3.5mg / cm 2 , 4.0mg / cm 2 , 5.0mg / cm 2 、6.0mg / cm 2 、8.0mg / cm 2 、9.0mg / cm 2 or any value therebetween. In some embodiments of the present invention, the loading amount of the composite material on the conductive substrate is 2.0 mg / cm 2 -8.5mg / cm 2 In some embodiments, the loading amount of the oxygen composite material on the conductive substrate is 2.5 mg / cm 2 -5.0mg / cm 2 .

[0010] In some embodiments, the conductive substrate is selected from one or more of carbon cloth, nickel mesh and nickel foam, preferably carbon cloth.

[0011] In a second aspect, the present invention provides a method for preparing a cerium copper cobalt oxide sulfide catalyst, comprising the following steps:

[0012] S1: immersing a substrate in a solution containing a cerium source, a copper source and a cobalt source, and performing electrochemical deposition to obtain a first precursor, wherein the first precursor contains hydroxides of copper and cobalt and cerium;

[0013] S2: subjecting the first precursor of step S1 to oxidation treatment to obtain a second precursor comprising cerium oxide and copper cobalt oxide;

[0014] S3: The second precursor of step S2 is subjected to a sulfidation treatment to obtain the cerium copper cobalt oxide sulfide catalyst.

[0015] According to some embodiments of the present invention, the preparation method of the above-mentioned catalyst includes first forming rare earth metal cerium and copper cobalt hydroxide precursors on a substrate by electrochemical co-deposition, oxidizing the above-mentioned precursors in a box furnace to obtain a heterostructure of cerium oxide and copper cobalt spinel oxide, and then achieving sulfidation by a hydrothermal method to obtain a product heterostructure of cerium oxide and copper cobalt spinel sulfide.

[0016] According to some embodiments of the present invention, in step S1, electrochemical deposition is performed using a three-electrode system, with Ag / AgCl as a reference electrode, platinum as a counter electrode, and carbon cloth as a working electrode.

[0017] According to some embodiments of the present invention, before the substrate is immersed in a solution containing a cerium source, a copper source and a cobalt source, the substrate surface can be washed with an acid solution, such as ultrasonic washing, and then washed with an organic solvent and water and dried. In some embodiments, the acid solution can be at least one of formic acid, acetic acid, sulfuric acid, and nitric acid. In some embodiments, the concentration of the acid solution is 0.5M (mol / L)-1.5M.

[0018] According to some embodiments of the present invention, the potential of the electrochemical deposition is -0.4V to -1.6V. In some specific embodiments, the potential of the electrochemical deposition can be -0.5V, -0.6V, -0.7V, -0.8V, -0.9V, -1.0V, -1.1V, -1.2V, -1.3V, -1.4V, -1.5V and any value therebetween. In some embodiments, the potential of the electrochemical deposition is -0.8V to -1.2V.

[0019] According to some embodiments of the present invention, the electrochemical deposition time is 1800s-5400s, such as 1900s, 2000s, 2100s, 2300s, 2500s, 2800s, 3000s, 4000s, 5000s, 5200s or any value therebetween. In some embodiments, the deposition time is 3000s-3600s.

[0020] According to some embodiments of the present invention, in step S2, the temperature of the oxidation treatment is 100°C-600°C, such as 150°C, 200°C, 250°C, 300°C, 400°C, 500°C or any value therebetween. In some embodiments, the temperature of the oxidation treatment is 250°C-350°C.

[0021] According to some embodiments of the present invention, the oxidation treatment time is 1 h-4 h, such as 1.5 h, 2.0 h, 2.5 h, 3.0 h, 3.5 h or any value therebetween. In some embodiments, the oxidation treatment time is 2.5 h-3.5 h.

[0022] According to some embodiments of the present invention, the oxidation treatment is performed in a box furnace.

[0023] According to some embodiments of the present invention, in step S3, the sulfurization treatment includes subjecting the second precursor to a hydrothermal reaction in the presence of a sulfur source.

[0024] According to some embodiments of the present invention, the temperature of the hydrothermal reaction is 70°C-150°C, such as 75°C, 80°C, 85°C, 90°C, 100°C, 110°C, 120°C, 140°C or any value therebetween. In some embodiments, the temperature of the hydrothermal reaction is 100°C-120°C.

[0025] According to some embodiments of the present invention, the hydrothermal reaction time is 6h-18h, such as 7h, 8h, 9h, 10h, 12h, 14h, 17h or any value therebetween. In some embodiments, the hydrothermal reaction time is 10h-12h.

[0026] According to some embodiments of the present invention, the molar ratio of the cerium source, the copper source and the cobalt source is 0.1:5:10-3:5:10, such as 0.1:5:10, 0.3:5:10, 0.5:5:10, 0.6:5:10, 0.9:5:10, 1:5:10, 3:5:10 or any value therebetween. In some embodiments, the molar ratio of the cerium source, the copper source and the cobalt source is 0.2:5:10-2:5:10.

[0027] According to some embodiments of the present invention, the cerium source is selected from soluble salts of cerium. In some embodiments, the cerium source is selected from cerium nitrate.

[0028] According to some embodiments of the present invention, the copper source is selected from copper nitrate and / or copper sulfate. In some embodiments, the copper source is selected from soluble salts of copper.

[0029] According to some embodiments of the present invention, the cobalt source is selected from cobalt nitrate and / or cobalt chloride. In some embodiments, the cobalt source is selected from soluble salts of cobalt.

[0030] According to some embodiments of the present invention, the sulfur source is selected from one or more of sodium sulfide, thiourea, and sublimed sulfur. In some embodiments, the sulfur source is selected from sodium sulfide.

[0031] According to some embodiments of the present invention, the substrate is a conductive substrate. In some embodiments, the substrate is selected from one or more of carbon cloth, nickel mesh and nickel foam, preferably carbon cloth.

[0032] According to some embodiments of the present invention, the method for preparing the cerium copper cobalt oxide sulfide catalyst comprises the following specific steps:

[0033] Step A, placing a substrate in a solution containing cerium salt, copper salt and cobalt salt, and performing electrochemical deposition through a three-electrode system to obtain an electro-oxidation benzyl alcohol catalyst hydroxide precursor;

[0034] Step B, oxidizing the above precursor in a box furnace to obtain a heterostructure of cerium oxide and copper-cobalt spinel oxide;

[0035] Step C, sulfiding the heterostructure of cerium oxide and copper-cobalt spinel oxide treated in step B by hydrothermal method in the presence of a sulfur source to obtain a heterostructure of cerium oxide and copper-cobalt spinel sulfide.

[0036] Preferably, the substrate is a conductive substrate selected from carbon cloth.

[0037] In a specific embodiment of the above method, in step A, the cerium salt is selected from cerium nitrate, the copper salt is selected from copper nitrate, and the cobalt salt is selected from cobalt nitrate.

[0038] In a specific embodiment of the above method, in step A, the molar ratio of the cerium salt, the copper salt and the cobalt salt is 0.2:5:10-2:5:10.

[0039] In a specific embodiment of the above method, in step A, the electrochemical deposition is performed at a potential of -0.8 V to -1.2 V. The deposition time is 3000 s to 3600 s.

[0040] In a specific embodiment of the above method, in step B, the oxidation temperature in the box furnace is 250° C.-350° C. The calcination time is 2.5 h-3.5 h.

[0041] In a specific embodiment of the above method, in step C, the vulcanization temperature is 100° C.-120° C. and the vulcanization time is 10 h-12 h.

[0042] In a third aspect, the present invention provides use of the cerium copper cobalt oxide sulfide catalyst described in the first aspect or the cerium copper cobalt oxide sulfide catalyst prepared by the preparation method described in the second aspect in the electrocatalytic oxidation of aromatic alkyl alcohols, preferably benzyl alcohol.

[0043] In some embodiments, the cerium copper cobalt oxide sulfide catalyst is used as an anode catalyst to oxidize benzyl alcohol to benzaldehyde or benzoic acid under alkaline conditions.

[0044] In a fourth aspect, the present invention provides a method for electrocatalytic oxidation of benzyl alcohol, comprising oxidizing benzyl alcohol to benzaldehyde or benzoic acid in the presence of the cerium copper cobalt oxide sulfide catalyst of the present invention.

[0045] In some embodiments, the oxidation is performed in a two-electrode system, wherein the working electrode in the two-electrode system comprises the cerium copper cobalt oxide sulfide catalyst described in the first aspect or the cerium copper cobalt oxide sulfide catalyst prepared by the preparation method described in the second aspect.

[0046] According to some embodiments of the present invention, the electrolyte (working conditions) in the two-electrode system is a mixed solution of a KOH aqueous solution with a molar fraction of 0.5M-1.5M and a benzyl alcohol aqueous solution with a molar fraction of 0.3M-0.7M.

[0047] In some embodiments, the counter electrode in the two-electrode system is selected from a platinum electrode.

[0048] The cerium oxide copper cobalt sulfide catalyst (electrooxidation benzyl alcohol catalyst) provided by the present invention comprises a substrate and a heterogeneous structure of cerium oxide and copper cobalt spinel sulfide grown thereon. The catalyst is a highly active anode catalyst of a rare earth metal, has high selectivity, a large surface area and a large number of active sites, so that the present invention has good catalytic performance for the directional conversion of benzyl alcohol into benzaldehyde or benzoic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Schematic diagram of the electrooxidation of benzyl alcohol to benzaldehyde and benzoic acid in the presence of a catalyst.

[0050] Figure 2 The X-ray diffraction pattern of the product prepared in Example 1 is shown in FIG.

[0051] Figure 3 This is a transmission electron microscope photograph of the product prepared in Example 1.

[0052] Figure 4 The linear sweep voltammetry curves of the products prepared in Example 1, Example 2 and Example 3 as catalysts to promote the electro-oxidation reaction of benzyl alcohol.

[0053] Figure 5This is the electrochemical impedance spectrum of the products prepared in Example 1, Example 2 and Example 3 as catalysts to promote the electro-oxidation reaction of benzyl alcohol.

[0054] Figure 6 This is the in-situ electro-oxidation Raman spectrum of the product prepared in Example 1.

[0055] Figure 7 This is the in-situ electro-oxidation infrared spectrum of the product prepared in Example 1. DETAILED DESCRIPTION

[0056] The present invention will be further described below by means of specific examples, but the scope of the present invention is not limited thereto.

[0057] The ultrapure water used in the experiment was of conductivity 18.25 MΩ, and the reagents used in the experiment were of analytical grade.

[0058] Main instruments and reagents used:

[0059] CHI760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) was used for linear sweep voltammetry test;

[0060] UPT laboratory ultrapure water device (Chengdu Ultrapure Technology Co., Ltd.), used to prepare ultrapure water;

[0061] Electronic balance (Shanghai Bo Le Mechanical and Electrical Equipment Co., Ltd.), used for weighing drugs;

[0062] A desktop X-ray diffractometer (Rigaku Corporation, MiniFlex600) was used for X-ray diffraction characterization;

[0063] Transmission electron microscopy, used for morphological characterization of benzyl alcohol electrooxidation catalyst;

[0064] Vacuum drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.);

[0065] KQ5200 ultrasonic cleaner (Kunshan Ultrasonic Instrument Co., Ltd.);

[0066] Working electrode: three-electrode system, Ag / AgCl (CHI Instruments, USA) as reference electrode, platinum as counter electrode;

[0067] Desktop drying oven (Chongqing Testing Equipment Factory);

[0068] Cobalt nitrate hexahydrate, cerium nitrate hexahydrate (Chengdu Kelong Chemical Co., Ltd.);

[0069] Copper nitrate trihydrate (Chengdu Kelong Chemical Reagent Factory);

[0070] Sodium sulfide nonahydrate (Tianjin Baishi Chemical Co., Ltd.);

[0071] Potassium hydroxide (Tianjin Damao Chemical Reagent Factory);

[0072] Benzyl alcohol (Tianjin Damao Chemical Reagent Factory);

[0073] Benzaldehyde (Tianjin Damao Chemical Reagent Factory);

[0074] Benzoic acid (Tianjin Damao Chemical Reagent Factory);

[0075] Carbon cloth (Shanghai Hesen Electric Co., Ltd.).

[0076] Example 1

[0077] A piece of 2×3cm 2 The carbon cloth was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0078] Place 20mL 0.1M Cu(NO3)2·3H2O aqueous solution, 40mL 0.1M Co(NO3)3·6H2O aqueous solution and 4mL 0.1M Ce(NO3)3·6H2O aqueous solution in a 100mL beaker and mix well. Immerse the pretreated carbon cloth material in the solution, connect it to the working electrode, react for 3600s at a voltage of -1.0V, and then take it out. Wash it with deionized water, and then dry it in a vacuum oven at 50℃ for 2h to obtain the rare earth metal Ce and CuCo2(OH)8 precursor, namely Ce-CuCo2(OH)8.

[0079] The above precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 10°C / min in a box furnace, calcined for 2 hours, and then cooled to room temperature at a cooling rate of 100°C / h to obtain CeO2 / CuCo2O4.

[0080] Sulfurization was performed by hydrothermal method. 40 mL of saturated Na2S aqueous solution was added to the lining of a 100 mL polytetrafluoroethylene autoclave, and then a piece of prepared CeO2 / CuCo2O4 was placed vertically. The reactor lining containing the solution was loaded into a stainless steel autoclave and transferred to an oven, heated to 120°C, kept constant for 12 hours, and then naturally cooled to room temperature. The carbon cloth after taking out the growth material was washed with a large amount of ultrapure water and dried at 50°C overnight to obtain catalyst 1, which was calculated as CeO2 / CuCo2S4.

[0081] In the above catalyst 1, the molar content of Ce is 7.04% based on CeO2 / CuCo2S4, and the loading amount of CeO2 / CuCo2S4 on the carbon cloth is 3.70 mg / cm 2 .

[0082] Example 2

[0083] A piece of 2×3cm 2 The carbon cloth was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0084] Place 20mL 0.1M Cu(NO3)2·3H2O aqueous solution, 40mL 0.1M Co(NO3)3·6H2O aqueous solution and 1mL 0.1M Ce(NO3)3·6H2O aqueous solution in a 100mL beaker and mix well. Immerse the pretreated carbon cloth material in the solution, connect it to the working electrode, react for 3600s at a voltage of -1.0V, and then take it out. Wash it with deionized water, and then dry it in a vacuum oven at 50℃ for 2h to obtain the rare earth metal Ce and CuCo2(OH)8 precursor, namely Ce-CuCo2(OH)8.

[0085] The above precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 10°C / min in a box furnace, calcined for 2 hours, and then cooled to room temperature at a cooling rate of 100°C / h to obtain CeO2 / CuCo2O4.

[0086] Sulfurization was performed by hydrothermal method. 40 mL of saturated Na2S aqueous solution was added to the lining of a 100 mL polytetrafluoroethylene autoclave, and then a piece of prepared CeO2 / CuCo2O4 was placed vertically. The reactor lining containing the solution was loaded into a stainless steel autoclave and transferred to an oven, heated to 120°C, kept at a constant temperature for 12 hours, and then naturally cooled to room temperature. The carbon cloth after taking out the growth material was washed with a large amount of ultrapure water and dried at 50°C overnight to obtain catalyst 2.

[0087] In the above catalyst 2, the molar content of Ce is 6.44% based on CeO2 / CuCo2S4, and the loading amount of CeO2 / CuCo2S4 on the carbon cloth is 4.90 mg / cm 2 .

[0088] Example 3

[0089] A piece of 2×3cm 2 The carbon cloth was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0090] Place 20mL 0.1M Cu(NO3)2·3H2O aqueous solution, 40mL 0.1M Co(NO3)3·6H2O aqueous solution and 8mL 0.1M Ce(NO3)3·6H2O aqueous solution in a 100mL beaker and mix well. Immerse the pretreated carbon cloth material in the solution, connect it to the working electrode, react for 3600s at a voltage of -1.0V, and then take it out. Wash it with deionized water, and then dry it in a vacuum oven at 50℃ for 2h to obtain the rare earth metal Ce and CuCo2(OH)8 precursor, namely Ce-CuCo2(OH)8.

[0091] The above precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 10°C / min in a box furnace, calcined for 2 hours, and then cooled to room temperature at a cooling rate of 100°C / h to obtain CeO2 / CuCo2O4.

[0092] Sulfurization was performed by hydrothermal method. 40 mL of saturated Na2S aqueous solution was added to the lining of a 100 mL polytetrafluoroethylene autoclave, and then a piece of prepared CeO2 / CuCo2O4 was placed vertically. The reactor lining containing the solution was loaded into a stainless steel autoclave and transferred to an oven, heated to 120°C, kept at a constant temperature for 12 hours, and then naturally cooled to room temperature. After taking out the grown material, the carbon cloth was washed with a large amount of ultrapure water and dried at 50°C overnight to obtain catalyst 3.

[0093] In the above catalyst 3, the molar content of Ce is 12.18% based on CeO2 / CuCo2S4, and the loading amount of CeO2 / CuCo2S4 on the carbon cloth is 4.10 mg / cm 2 .

[0094] Comparative Example 1

[0095] A piece of 2×3cm 2 The carbon cloth was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0096] Place 20mL of 0.1M Cu(NO3)2·3H2O aqueous solution and 40mL of 0.1M Co(NO3)3·6H2O aqueous solution in a 100mL beaker, and immerse the pretreated carbon cloth in the above solution. Connect it to the working electrode, react at a voltage of -1.0V for 3600s, and then take it out. Wash it with deionized water, and then dry it in a vacuum oven at 50℃ for 2h to obtain the CuCo2(OH)8 precursor.

[0097] The precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 10°C / min in a box furnace, calcined for 2 hours, and then cooled to room temperature at a cooling rate of 100°C / h to obtain CuCo2O4.

[0098] Sulfurization was performed by hydrothermal method. 40 mL of saturated Na2S aqueous solution was added to the lining of a 100 mL polytetrafluoroethylene autoclave, and then a piece of prepared CuCo2O4 was placed vertically. The reactor lining containing the solution was placed into a stainless steel autoclave and transferred to an oven, heated to 120°C, kept constant for 12 hours, and then naturally cooled to room temperature. The carbon cloth after taking out the growth material was washed with a large amount of ultrapure water and dried at 50°C overnight to obtain a comparative catalyst, which was calculated as CuCo2S4.

[0099] Comparative Example 2

[0100] A piece of 2×3cm 2 The carbon cloth was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0101] Place 20mL 0.1M Cu(NO3)2·3H2O aqueous solution, 40mL 0.1M Co(NO3)3·6H2O aqueous solution and 2mL 0.1M Ce(NO3)3·6H2O aqueous solution in a 100mL beaker and mix well. Immerse the pretreated carbon cloth material in the solution, connect it to the working electrode, react for 3600s at a voltage of -1.0V, and then take it out. Wash it with deionized water and then dry it in a vacuum oven at 50℃ for 2h to obtain Ce-CuCo2(OH)8 precursor.

[0102] The above precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 10°C / min in a box furnace, calcined for 2 hours, and then cooled to room temperature at a cooling rate of 100°C / h to obtain a comparative catalyst, calculated as CeO2 / CuCo2O4.

[0103] In the above catalyst, the molar content of Ce is 7.76% based on CeO2 / CuCo2O4, and the loading amount of CeO2 / CuCo2O4 on the carbon cloth is 3.32 mg / cm 2 .

[0104] Comparative Example 3

[0105] A piece of 2×3cm 2 The carbon cloth was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0106] Place 20mL of 0.1M Cu(NO3)2·3H2O aqueous solution and 40mL of 0.1M Co(NO3)3·6H2O aqueous solution in a 100mL beaker and mix well. Immerse the pretreated carbon cloth material in the solution, connect it to the working electrode, react for 3600s at a voltage of -1.0V, and then take it out. Wash it with deionized water and then dry it in a vacuum oven at 50℃ for 2h to obtain the CuCo2(OH)8 precursor.

[0107] The above precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 10°C / min in a box furnace, calcined for 2 hours, and then cooled to room temperature at a cooling rate of 100°C / h to obtain a comparative catalyst, calculated as CuCo2O4.

[0108] Comparative Example 4

[0109] A piece of 2×3cm 2 The platinum sheet was placed in a 1M nitric acid solution and ultrasonicated for several minutes. After being taken out, it was washed several times with ethanol and water and dried in a vacuum drying oven at 50°C.

[0110] Test Example 1

[0111] The products obtained in Example 1, Example 2 (and Example 3) were respectively cut into 0.5 cm × 1 cm pieces and clamped on an electrode clamp as a working electrode, platinum was used as a counter electrode, and the two electrodes were inserted into a mixed solution of 1 M KOH and 0.1 M benzyl alcohol to carry out an electro-oxidation reaction of benzyl alcohol. The potential window was scanned in the range of -0.4 V to -1.6 V at a scanning rate of 2 mV / s to obtain a conversion curve of benzyl alcohol, as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the catalyst prepared in Example 1 has a lower benzyl alcohol oxidation overpotential than that of Examples 2 and 3, and thus has a higher electrocatalytic activity for benzyl alcohol oxidation.

[0112] Test Example 2

[0113] The products obtained in Example 1 were cut into 0.5 cm × 1 cm pieces and clamped on electrode clamps as working electrodes, platinum was used as counter electrode, and the two electrodes were inserted into a mixed solution with a molar concentration of 1 M KOH and 0.1 M benzyl alcohol to carry out electro-oxidation reaction of benzyl alcohol. The yield of benzyl alcohol electro-oxidation to benzaldehyde is shown in Table 1.

[0114] Table 1

[0115]

[0116] Test Example 3

[0117] The electrochemical impedance spectra of the products prepared in Example 1, Example 2 and Example 3 as catalysts to promote the electrooxidation reaction of benzyl alcohol are as follows: Figure 5 As shown. Figure 5 It can be seen that the catalyst prepared in Example 1 has a smaller electrochemical impedance than that of Example 2 and Example 3, and the lower the charge transfer impedance, the higher the electrocatalytic activity of benzyl alcohol oxidation.

[0118] Test Example 4

[0119] The in-situ electro-oxidation Raman spectrum of the catalyst of Example 1 during the catalytic reaction is shown in FIG. Figure 6 As shown. Figure 6 It can be seen that the catalyst of Example 1 is in situ reconstructed to produce highly active species during the catalytic reaction, thereby further improving the catalytic reaction activity.

[0120] Figure 7 The in situ infrared spectrum in also shows the in situ adsorption and conversion process of the catalyst of Example 1 on the intermediate and benzyl alcohol during the reaction, confirming the effect of the catalyst of Example 1 on the electrosynthesis of aromatic compounds.

[0121] It can be seen from the above examples and the accompanying drawings that the electro-oxidation benzyl alcohol catalyst of the present invention has good electro-oxidation activity.

[0122] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.

Claims

1. A cerium oxide copper cobalt sulfide catalyst, comprising a conductive substrate and a composite material supported on the conductive substrate, wherein the composite material comprises cerium oxide and copper cobalt sulfide.

2. The cerium copper cobalt oxide sulfide catalyst according to claim 1, characterized in that Based on the total molar amount of cerium oxide and copper cobalt sulfide, the molar content of the cerium element is 1%-45%, preferably 1%-35%, more preferably 1%-20%, for example 5%-15% or 6.5%-10%.

3. The cerium copper cobalt oxide sulfide catalyst according to claim 1 or 2, characterized in that: The loading amount of the composite material on the conductive substrate is 1 mg / cm 2 -10 mg / cm 2 , preferably 2.5 mg / cm 2 -5 mg / cm 2 ; and / or The conductive substrate is selected from one or more of carbon cloth, nickel mesh and nickel foam.

4. The cerium copper cobalt oxide sulfide catalyst according to any one of claims 1 to 3, characterized in that: The composite material has a nanosheet-like morphology, preferably a hexagonal nanosheet-like morphology.

5. A method for preparing a cerium copper cobalt oxide sulfide catalyst, comprising the following steps: S1: immersing a conductive substrate in a solution containing a cerium source, a copper source and a cobalt source for electrochemical deposition to obtain a first precursor, wherein the first precursor contains hydroxides of copper and cobalt and cerium; S2: subjecting the first precursor of step S1 to oxidation treatment to obtain a second precursor comprising cerium oxide and copper cobalt oxide; S3: The second precursor of step S2 is subjected to a sulfidation treatment to obtain the cerium copper cobalt oxide sulfide catalyst.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the cerium source, the copper source and the cobalt source is 0.1:5:10-3:5:10, preferably 0.5:5:10-2:5:

10.

7. The preparation method according to claim 5 or 6, characterized in that: In step S1, the potential of the electrochemical deposition is -0.4V to -1.6V, and the time of the electrochemical deposition is 1800s to 5400s; and / or In step S2, the oxidation treatment temperature is 100°C-600°C, and the oxidation treatment time is 1h-4h; and / or In step S3, the sulfurization treatment includes subjecting the second precursor to a hydrothermal reaction in the presence of a sulfur source. Preferably, the temperature of the hydrothermal reaction is 70° C.-150° C., and the time of the hydrothermal reaction is 6 h-18 h.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The cerium source is selected from soluble cerium salts, preferably cerium nitrate; and / or The copper source is selected from soluble copper salts, preferably copper nitrate and / or copper sulfate; and / or The cobalt source is selected from soluble cobalt salts, preferably cobalt nitrate and / or cobalt chloride; and / or The sulfur source is selected from one or more of sodium sulfide, thiourea and sublimated sulfur; and / or The conductive substrate is selected from one or more of carbon cloth, nickel mesh and nickel foam.

9. Use of the cerium copper cobalt oxide sulfide catalyst according to any one of claims 1 to 4 or the cerium copper cobalt oxide sulfide catalyst prepared by the preparation method according to any one of claims 5 to 8 in the electrocatalytic oxidation of aromatic alkyl alcohols, preferably benzyl alcohol.

10. A method for electrocatalytically oxidizing benzyl alcohol, comprising oxidizing benzyl alcohol to benzaldehyde and / or benzoic acid in the presence of the cerium copper cobalt oxide sulfide catalyst described in claims 1 to 4 or the cerium copper cobalt oxide sulfide catalyst prepared by the preparation method of any one of claims 5 to 8, Preferably, the oxidation is carried out in a two-electrode system, wherein the working electrode in the two-electrode system comprises the cerium copper cobalt oxide sulfide catalyst described in claims 1-4 or the cerium copper cobalt oxide sulfide catalyst prepared by the preparation method described in any one of claims 5-8, and the electrolyte comprises a 0.5M-1.5M KOH aqueous solution and a 0.05M-0.3M benzyl alcohol aqueous solution.